Perancangan Server-Side Website E-Commerce Menggunakan Metode Waterfall pada PT Bizhub Digital Indonesia - Aziz, Muhammad Hilmy; Wicaksono, Bagus Satrio; Nurdianto, Muhammad Akbar; Rakhmadi, Ardhon (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
PT Bizhub Digital Indonesia previously relied on third-party affiliate platforms for its promotional activities. This reliance incurred additional operational costs and limited the company's control over centralized partner management. This study aims to design and implement a server-side infrastructure (REST API) for an e-commerce platform with an independent affiliate feature to resolve these operational issues. The system development adopted the Waterfall method, which includes requirements analysis, system design, implementation, and testing. The backend infrastructure was built using the Hono.js framework, TypeScript language, and Bun runtime environment. The design resulted in 16 relational database tables and 12 API module groups documented via Swagger UI. Core functionalities include JSON Web Token (JWT) authentication, order management, and payment gateway integration via webhook to automate payment status conversion and affiliate commission distribution in real-time. Functional evaluation using Black-Box Testing on 54 API endpoints demonstrated a 100% operational success rate. The resulting system is proven reliable and capable of reducing third-party dependency, providing operational control efficiency, and enhancing the transparency of the company's financial reporting.